The Influence of Tokopedia Advertising Exposure and Persuasive Exposure Group Reference Towards Online Shop Tokopedia.com Access Behaviour - Asep Virgo; Tandiyo Pradekso, M.Sc (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
The amounts of advertising spending and rising intensity of Tokopedia advertising on television lead to rise the probability of mass getting exposed by Tokopedia advertising. This causing the emersion of mass behavior to following the advertising message from the television ads to access on Tokopedia.com. But the advertisement is not the only reason for people accessing Tokopedia website, there is another factor such as the persuasive exposure from reference group. The purpose of this research is to knowing the exposure influence of Tokopedia advertisement and persuasive exposure reference group towards the behavior of accessing online shop Tokopedia.com. Theory used in this research is the Advertising Exposure Model Theory. The Type of this research is explanatory research. This research using non-random and accidental sample collecting method, with total 50 sample of respondent. Testing instrument used for testing the hypothesis is simple linear statistic regression test. In this linear regression analytic, the classic assumption testing that become the requirements for the regression testing can be procced as not fulfilled, so the analysis is downgraded become the correlation analysis with using the Pearson correlation analysis. The Hypothesis test showed the significant value of advertising exposure variable by 0,389, and 0,217 for the significant value of persuasive exposure reference group variable. All the significant values are lower than α (0,05), so the both variable are not connected to the behavior of accessing the Tokopedia Online Shop website, Tokopedia.com. The conclusion of this research is for creating some advices to Tokopedia to lower the advertisements on television and change into other marketing strategy to bring mass for accessing the Tokopedia Online Shop.